2020
DOI: 10.5194/bg-17-3099-2020
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of aboveground litter for soil organic matter formation – a soil profile perspective

Abstract: Abstract. In contrast to mineral topsoils, in subsoils the origin and processes leading to the formation and stabilization of organic matter (OM) are still not well known. This study addresses the fate of litter-derived carbon (C) in whole soil profiles with regard to the conceptual cascade model, which proposes that OM formation in subsoils is linked to sorption–microbial processing–remobilization cycles during the downward migration of dissolved organic carbon (DOC). Our main objectives were to quantify the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 72 publications
(97 reference statements)
3
22
0
1
Order By: Relevance
“…Thus, POM clearly has a higher potential to fuel denitrification than MOM. This is well in line with previous studies showing that MOM comprises mainly less bioavailable C compounds (e.g., Kalbitz et al, 2005;Liebmann et al, 2020). Correspondingly, we found that only 22-28% of the initial WEOC in soils with MOM addition was emitted as CO 2 within 24 h, while 37-63% of initial WEOC was mineralized in soils with POM addition.…”
Section: Effect Of Organic Matter Fractions On Potential Denitrification and Co 2 Productionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, POM clearly has a higher potential to fuel denitrification than MOM. This is well in line with previous studies showing that MOM comprises mainly less bioavailable C compounds (e.g., Kalbitz et al, 2005;Liebmann et al, 2020). Correspondingly, we found that only 22-28% of the initial WEOC in soils with MOM addition was emitted as CO 2 within 24 h, while 37-63% of initial WEOC was mineralized in soils with POM addition.…”
Section: Effect Of Organic Matter Fractions On Potential Denitrification and Co 2 Productionsupporting
confidence: 92%
“…Thus, MOM represents a continuum of mineral-bound C substances of varying availability and degradability (e.g., Mikutta et al, 2007). Especially in topsoils with high OC inputs and mineral C loadings, OC can repeatedly be displaced and desorbed from mineral surfaces (Leinemann et al, 2016;Liebmann et al, 2020). Consequently, MOM is a potential source of OC fueling denitrification, with its contribution probably depending on the amount and quality of WEOC.…”
Section: Introductionmentioning
confidence: 99%
“…Subsoils are unsaturated in OM due to little inputs, such as DOC from upper soil horizons, root-derived and already microbially processed OM, but large mineral surfaces (Kaiser and Kalbitz, 2012;Lützow et al, 2006). Therefore, the probability of mobilized PyOM to interact with the mineral phase is higher in the subsoil, resulting in a higher retention compared to topsoils where OM is already occupying sorption sites on the mineral surfaces.…”
Section: Pyom Retention In Soilmentioning
confidence: 99%
“…Compost application is associated both with high levels of mobile DOC (Wright et al, 2008;Zmora-Nahum et al, 2005), as well as a large proportion of aromatic functional groups, attributed to high amounts of lignin and other biomolecules (Leifeld et al, 2002). Research into the transport of organic molecules, such as described by the "cascade theory", has shown that "fresh" carbon inputs are preferentially retained within the top 30 cm (Liebmann et al, 2020) and that aromatic moieties are rapidly removed from the soil solution at the surface (Leinemann et al, 2018). This removal may be a function of the relatively low solubilities of non-polar aromatic functional groups (Maxin and Kogel-Knabner, 1995), as well as their tendency to partition into other non-polar, insoluble organic matter (Pignatello, 1999).…”
Section: Compost + Cover Crops Increased Doc and Aromatic Carbon In Smentioning
confidence: 99%
“…Carbon inputs to subsurface soils are primarily through dissolved organic carbon (DOC) movement (Kaiser and Kalbitz, 2012) and deeper rooting biomass and exudates (Sokol and Bradford, 2019). This contrasts with the greater variety of inputs to surface soils such as compost (White et al, 2020a), plant aboveground biomass/shoots (Liebmann et al, 2020), atmospheric deposition (Mladenov et al, 2012) and abundant shallower root biomass (Poeplau and Don, 2015).…”
Section: Introductionmentioning
confidence: 99%